Comparative phytochemical analysis of five Egyptian strawberry cultivars (Fragaria × ananassa Duch.) and antidiabetic potential of Festival and Red Merlin cultivars. Issue 27 (6th May 2021) - El-Hawary, Seham S.; Mohammed, Rabab; El-Din, Marwa Emad; Hassan, Hossam M.; Ali, Zeinab Y.; Rateb, Mostafa E.; Bellah El Naggar, El Moataz; Othman, Eman M.; Abdelmohsen, Usama Ramadan
Abstract : This work aims to explore the differences in phytochemical composition and biological properties of five strawberry hybrids ( Fragaria × ananassa Duch.), and highlights the non-edible part (byproduct) as a source of self-remedy natural herb along with fruits. Abstract : This work aims to explore the differences in phytochemical composition and biological properties of five strawberry hybrids ( Fragaria × ananassa Duch.), and highlights the non-edible part (byproduct) as a source of self-remedy natural herb along with fruits. HPLC/DAD/HRESIMS technique was used in the dereplication of ten ethanolic extracts of five strawberry cultivars leaves and fruits (Festival, Red Merlin, Suzana, Tamar and Winter Dawn). Total phenolic and total flavonoid contents were established using Folin–Ciocalteu and aluminum chloride colorimetric assays, respectively. Ethanolic extracts of leaves and fruits from Festival and Red Merlin cultivars were selected to investigate their anti-hyperglycemic activity using streptozotocin-induced diabetic rats. Oxidative stress markers, lipid profile and kidney and liver function tests were assessed. The results revealed different chemical profiles of ten samples with the identification of 37 metabolites, represented mainly as flavonoids and phenolic acid derivatives. Phytochemical investigation resulted in the isolation of seven known phenolic compounds; quercetin, kaempferol, p -coumaric acid, p -tyrosol, methyl gallate, trans -tiliroside and eutigoside A. Suzana cultivar was the richest cultivar with flavonoids and total phenolics except for the total flavonoid content in leaves referred to Festival cultivar. Ethanolic extract of leaves, especially Festival cultivar was the most bioactive one. The results established the role of strawberry leaves along with fruits as an antioxidant and hypoglycemic natural remedy.